2003
DOI: 10.1016/j.rmed.2003.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Assay of pleural fluid interleukin-6, tumour necrosis factor-alpha and interferon-gamma in the diagnosis and outcome correlation of tuberculous effusion

Abstract: Pleural fluid IL-6, TNF-alpha and IFN-gamma assays are useful in the diagnosis of pleural TB. The initial IL-6 level correlates with the number of febrile days. The percentage change of cytokines after 2 weeks of treatment also helps to predict residual pleural scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 31 publications
7
37
0
1
Order By: Relevance
“…Moreover, it is well mentioned in few studies that other diseases can also cause elevated INF-γ levels in PF such as haematologic malignancies and empyema. 24,25 The higher sensitivity and specificity of INF-γ as compared to ADA in this study was found to be in total agreement with the existing studies which reported PF INF-γ levels to be more sensitive and specific than ADA 28 and suggested INF-γ as a better marker than ADA for the diagnosis of tuberculous pleuritis.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it is well mentioned in few studies that other diseases can also cause elevated INF-γ levels in PF such as haematologic malignancies and empyema. 24,25 The higher sensitivity and specificity of INF-γ as compared to ADA in this study was found to be in total agreement with the existing studies which reported PF INF-γ levels to be more sensitive and specific than ADA 28 and suggested INF-γ as a better marker than ADA for the diagnosis of tuberculous pleuritis.…”
Section: Discussionsupporting
confidence: 91%
“…This condition results in limited inflammation. Predicted ranges for IFN-␥ and IL-10 correlate with studies measuring cytokine levels at the site of disease (47,53,54), whereas simulated IL-4 is present at essentially undetectable levels during latency (Ͻ0.1 pg/ml), possibly explaining why IL-4 is difficult to detect in humans with latent infection (54,55). IL-12 levels in this particular latency simulation are higher than what might be found within the lungs, but this is likely due to the constraints of modeling within a single compartment, which means that priming of the T cell response occurs in the lungs instead of lymph nodes in this model.…”
Section: Latent Infectionmentioning
confidence: 83%
“…In the past, several biological markers have been studied to aid the diagnosis of plTB, including the measurement of pleural fluid concentrations of adenosine deaminase [50,51], tumour necrosis factor-a [52][53][54] and whole IFN-c [50,55,56], with reported diagnostic sensitivities ranging from 72-88% and specificities from 88-100% [50][51][52][53][54][55][56]. Thus, reported sensitivities of adenosine deaminase and IFN-c measurements in PE for the diagnosis of plTB are similar to the sensitivity of the T-SPOT.TB test reported in the present study, although T-SPOT.TB specificity seems lower.…”
Section: Discussionmentioning
confidence: 99%